1992
DOI: 10.1002/jmv.1890360206
|View full text |Cite
|
Sign up to set email alerts
|

Replication of hepatitis B virus in differentiated adult rat hepatocytes transfected with cloned viral DNA

Abstract: The possibility of obtaining expression of human hepatitis B virus (HBV) genes and production of virus particles in normal liver cells from heterologous species like normal adult rat hepatocytes, by transfecting the complete HBV genome, was investigated. Various techniques for hepatocyte transfection were assayed including the usual calcium-phosphate coprecipitation technique, the Pasco and Fagan modified calcium-phosphate procedure, and the lipofection technique. Transfection efficiency was determined by meas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
10
0

Year Published

1993
1993
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 46 publications
3
10
0
Order By: Relevance
“…1). These results are consistent with other published studies that have used similar isolation and culture techniques to maintain differentiated rat hepatocytes (7,22,23,29,36,69).…”
Section: Confirmation Of Hepatocyte Differentiation In Culturesupporting
confidence: 92%
See 2 more Smart Citations
“…1). These results are consistent with other published studies that have used similar isolation and culture techniques to maintain differentiated rat hepatocytes (7,22,23,29,36,69).…”
Section: Confirmation Of Hepatocyte Differentiation In Culturesupporting
confidence: 92%
“…We have characterized HBx regulation of apoptosis in cultured primary rat hepatocytes, a biologically relevant system for studying hepatocyte physiology and apoptosis (7,12,22,25,29,36,69). This model system circumvents potential problems associated with previously reported studies in HBx transgenic mice or in transformed or immortalized cell lines.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Primary rat hepatocytes are a biologically relevant model system used to study normal hepatocyte physiology and liver diseases (7,18,21,30,52). Our studies addressed the effect of HBx on the levels and activities of cell cycle-regulatory proteins and on overall cell cycle progression and linked HBxinduced modulation of cell proliferation pathways to cytosolic calcium signaling.…”
mentioning
confidence: 99%
“…Indeed, hepatocytes from refractory species are able to support viral replication only if the normal pathway of viral entry is artificially bypassed. Thus, it has been shown that primary rat hepatocytes or a rat hepatoma cell line could support HBV replication upon transient transfection of cloned HBV DNA (8,39). Complete virions are also produced in hepatocytes of HBV transgenic mice (10,17,43), while there is no evidence for reinfection by the circulating virus.…”
mentioning
confidence: 99%